Educação etnomatemática nas escolas indígenas karajá de xambioá. - AGUIAR, Haylla Rodrigues de (Universidade Federal do Tocantins, 2023)
This work had as objective the investigative study of the Karajá Xambioá Indigenous community's educational reality of Tocantins and displays ethnographic data collected in the community about what the Indians consider as a differentiated education from the age-old knowledge and cultural practices, the collection of information have taken place through oral accounts of indigenous teacher. Highlighting the need to develop a study on the teaching and learning process that seeks to take into account the mathematics produced in the cultural and social context of this indigenous community, for better learning in indigenous schools as in the non-indigenous. Proposed the use of intercultural knowledge for a better understanding of the teaching and learning of mathematics in indigenous schools. This reflection is based on the research program in Ethnomathematics, taking as its main theoretical work of D'ambrosio 1990.